Makna Tiga Lirik Lagu Mayumi Itsuwa (Telaah Stilistika Bahasa dalam Bahasa Jepang) - Suyanti Natalia; Fadhil Irsyad (Universitas Nasional, 2022)
This research was conducted to determine the meaning of denotation and connotation contained in the songs Kokoro No Tomo, Amayadori, and Koibito Yo by Mayumi Itsuwa. The method used to analyze these three songs is a descriptive method, which is a method that is carried out by describing facts which are then compiled with an analysis of the denotative and connotative meanings of words by Gorys Keraf and stylistic theory by Nyoman Kuta Ratna. As a result of this research, the authors found different meanings contained in the three songs. In the meaning of the lyrics of the song Kokoro No Tomo, namely love which has the meaning of love and affection, then there is also the symbol of Nina Bobo which has the meaning of putting children to sleep with singing and pleasing others with high statements or promises. Then in the lyrics of the song Amayadori there is also a symbol of forgiveness which has the meaning of giving forgiveness for mistakes and does not consider wrong again, and there is also a symbol of meeting which has the meaning of meeting, meeting and face to face, while in the song Koibito Yo, there is symbol that shows affection which so deep into her lover. Penelitian ini dilakukan untuk mengetahui makna denotasi dan konotasi yang terdapat pada lagu Kokoro No Tomo, Amayadori, dan Koibito Yo karya Mayumi Itsuwa. Metode yang digunakan untuk menganalisis ketiga lagu ini adalah metode deskriptif, yaitu metode yang dilakukan dengan cara mendeskripsikan fakta-fakta yang kemudian disusun dengan analisis dari makna kata secara denotatif dan konotatif oleh Gorys Keraf dan teori stilistika oleh Nyoman Kuta Ratna. Sebagai hasil dari penelitian ini, penulis menemukan makna yang berbeda yang terdapat pada ketiga lagu tersebut. Di makna pada lirik lagu Kokoro No Tomo, yaitu cinta yang memiliki makna suka sekali dan sangat sayang, lalu terdapat pula simbol Nina Bobo yang memiliki makna menidurkan anak dengan nyanyian dan menyenangkan hati orang lain dengan pernyataan atau janji yang tinggi. Kemudian di dalam lirik lagu Amayadori terdapat pula simbol memaafkan yang memiliki makna memberi ampun atas kesalahan dan tidak menganggap salah lagi, serta terdapat pula simbol pertemuan yang memiliki makna berjumpa, bersua dan berhadapan muka, sedangkan dalam lagu Koibito Yo, ada simbol yang menunjukkan rasa sayang yang begitu dalam terhadap kekasihnya.